Racial and Ethnic Identity: Social Scientific and Biblical Perspectives in Dialogue - Reese, Ruth Anne (The Asbury journal, 2010)
The first part of the paper lays out our understanding of ethnicity and race in light of current research from sociology and anthropology. The paper then turns to the New Testament material, and it examines "the Jews" as one ethnic group in the first century. This material is used to demonstrate that Christians also took on the language of ethnicity. The paper raises the question, "is there a Christian identity that both supersedes and subsumes ethnic identity?" It proposes that the answer to that question is, ''Yes, there is a Christian identity and ethos that supersedes ethnic identity." And, this paper will also argue that not all ethnic or cultural markers must be given up in order to be Christian. In the early Church, there were those who argued that a new Christian must take on the marks of Jewish ethnic identity; however, Paul successfully argued that Christians formed their own ethnic identity without having to give up all the former markers of their previous ethnic identity, whether Jew or Gentile.